تقييم أثر زيادة دعامة إضافية على ثبات التعويض الجزئي الثابت باستخدام نوعين من الإسمنت (دراســة مخـبرية) - عربي كاتبي, محمد (Latakia University Journal -Medical Sciences Series, 2019)
كان الهدف من هذه الدراسة التجريبية تقييم أثر وجود دعامة إضافية على ثبات التعويض الجزئي الثابت وذلك باستخدام إسمنتي فوسفات الزنك والبولي كربوكسيلات, وكذلك قارنت دراستنا بين المادتين المستخدمتين في إلصاق الجسور وقدرتهما على التثبيت، تم تحضير جسور على أسنان فرازاكو بدعامتين ( الضاحك الثاني السفلي الأيمن والرحى الثانية السفلية اليمنى وكان السن المفقود الرحى الأولى السفلية اليمنى) لاستقبال تعويض ثابت معدني كامل, وتم استنساخ أربعة وعشرين مثالاً من الفرازاكو بواسطة الطبعات المطاطية التي صبت بواسطة الأكريل الذاتي التصلب. تم تصنيع أربعة وعشرين جسراً كل منها مؤلفٌ من ثلاث قطع, قسمت هذه المجموعة إلى فئتين متساويتين، ألصقت الفئة الأولى بإسمنت فوسفات الزنك وألصقت الثانية بإسمنت بولي كربوكسيلات وقيست قوة التثبيت بواسطة جهاز الاختبارات العام. وباستخدام اختبار t ستيودنت الإحصائي أظهرت النتائج أن قوة فك الالتصاق للفئة الأولى من هذه المجموعة 21.83 كغ والفئة الثانية 17.67 كغ. تمت إضافة دعامة أخرى على مثال الفرازاكو ذي الدعامتين الأوليتين هي الضاحك الأول السفلي الأيمن، واستنسخ منه أربعة وعشرين مثالاً بنفس الطريقة السابقة, صنع لها أربعة وعشرون جسراً كل جسر مؤلف من أربع قطع، قسمت لفئتين متساويتين ألصقت الفئة الأولى بإسمنت فوسفات الزنك وألصقت الفئة الثانية بإسمنت بولي كربوكسيلات وقيست قوة التثبيت بواسطة جهاز الاختبارات العام, وكانت النتيجة أن المعدل الوسطي لقوة فك الالتصاق 29.71 كغ للفئة الأولى و 22.84 كغ للفئة الثانية. بينت نتائج الاختبار أن وجود دعامة إضافية قد زاد بشكل جوهري قوى الثبات للتعويض، وأن مادة إسمنت فوسفات الزنك هي أفضل من بولي كربوكسيلات في تثبيت التعويضات الثابتة. The purpose of this experimental study was to evaluate the effect of adding an extra abutment on retention of fixed partial denture by using Zinc Phosphate cement and polycarboxylate cement. Our study also compares between these two materials we used to cement the bridges and there retention ability. Two abutments were prepared of Acrylic teeth (The second right premolar, the second right molar, and the missing tooth was the First right molar) to receive cast metal complete fixed denture. Twenty four copies were made from the master cast using rubber impressions and then they were filled with self cured acrylic resin. Twenty four Bridges were made, each one consists of three pieces and divided to two equal groups (of 12). the First group cemented with Zinc phosphate cement and the second with polycarboxylate cement. The retention value was measured using Instron Universal Testing Machine. By using t student test analysis the results showed that the retention force of zinc phosphate cement in this group was 21.83kg and it was 17.67kg for polycarboxylate cement. After adding an extra abutment to the two initial abutments (the first right premolar). Twenty four copies were made from the master cast and twenty four Bridges were fabricated, each one consist of four Units, divided to two equal groups. The First group was cemented with Zinc phosphate cement and the second with polycarboxylate. Tensile strength was measured using Instron Universal Testing Machine. The results showed that the retention force of zinc phosphate cement in this group was 29.71kg and it was 22.84 kg for polycarboxylate cement. Due to the limitations of this study two results were detected: the first is that the presence of extra abutment increased significantly the retention force. The second is the retention value of Zinc phosphate cement was significantly greater than polycarboxylate cement.